Ranking five models of laptops using Fuzzy PROMETHEE / Wan Nur Syahirah Wan Muhammad Sukardi and Raihana Zainordin - Wan Muhammad Sukardi, Wan Nur Syahirah; Zainordin, Raihana (College of Computing, Informatics and Media, UiTM Perlis, 2023)
In modern college classrooms, computers are a common sight. Laptops are apparently brought by students as a learning aid since they make e-books easily accessible, can replace handwritten notes, enable rapid online access to material relating to the day's lecture, and allow for quick computations for arithmetic or statistics issues. It is crucial to research students' needs in this study. Four key features—price, battery, storage, and weight—were identified by several students after observation and comments. That’s why, it is prior to looking at other characteristics, this is a crucial quality to consider while choosing the finest laptop model. This research has considered five brands of laptops from five different companies. This research has three goals in mind. Foremost, to determine the most important criterion for buying a laptop. In addition, the study aims to rank laptop brands using the fuzzy Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) and its final objective is to compare the fuzzy PROMETHEE ranking with the original ranking. Twenty respondents are required to evaluate this issue using linguistic variables ranging from “very poor” to “very good”. The components are ordered using Fuzzy PROMETHEE. The findings of this study might be beneficial to many students. Future research might broaden the scope of the project by including a variety of criteria and objectives.